Peranan Spiritual Dalam Rawatan Paliatif: The Role of Spirituality in Palliative Care - Chik, Hasimah; Sa’ari, Che Zarrina; Chin, Loh Ee (Afkar: Jurnal Akidah dan Pemikiran Islam, 2017)
Spirituality is an element in palliative care in addition to physical, mental and social elements. Every element in palliative care has the roles and interests necessary to improve the quality of care. Spirituality can have a great impact on one’s life. The purpose of article that utilized content analysis method through literature study is to discuss in-depth spiritual themes and their importance in palliative care. The study finds the effort to achieve maximum impact in the treatment of patients requires the cooperation of patients, family members, friends and medical practitioners. Spirituality is believed to be of great contribution to the improvement of the quality of life, as spiritual inferiority can bring many problems and distresses. The psychotherapy element is an alternative to helping in emphasizing the aspect of spirituality towards the patients.